2016
DOI: 10.1038/cddis.2016.12
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Fas apoptosis inhibitory molecule leads to spontaneous obesity and hepatosteatosis

Abstract: Altered hepatic lipogenesis is associated with metabolic diseases such as obesity and hepatosteatosis. Insulin resistance and compensatory hyperinsulinaemia are key drivers of these metabolic imbalances. Fas apoptosis inhibitory molecule (FAIM), a ubiquitously expressed antiapoptotic protein, functions as a mediator of Akt signalling. Since Akt acts at a nodal point in insulin signalling, we hypothesize that FAIM may be involved in energy metabolism. In the current study, C57BL/6 wild-type (WT) and FAIM-knocko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…Regarding the absence of FAIM‐S and FAIM‐L in nervous system, mice did not show any obvious neuronal phenotype, although it was not specifically analyzed (Huo et al . ).…”
Section: Faim1mentioning
confidence: 97%
See 1 more Smart Citation
“…Regarding the absence of FAIM‐S and FAIM‐L in nervous system, mice did not show any obvious neuronal phenotype, although it was not specifically analyzed (Huo et al . ).…”
Section: Faim1mentioning
confidence: 97%
“…A recently published study by the same group reported that FAIM-KO mice developed spontaneous non-hyperphagic obesity, an increased fatty acid synthesis in liver, and reduced insulin receptor beta, suggesting the involvement of FAIM-S in energy homeostasis and insulin signaling. Regarding the absence of FAIM-S and FAIM-L in nervous system, mice did not show any obvious neuronal phenotype, although it was not specifically analyzed (Huo et al 2016).…”
Section: Faim1mentioning
confidence: 99%
“…These mice were normal with respect to development, survival, and phenotype. They were not obese and thus differed from the FAIM KO mice constructed by Huo et al (2009Huo et al ( , 2016. We examined skin-derived fibroblasts which have been shown to be susceptible to menadione- (Shalini et al, 2012) and arsenite- (Harada et al, 2008;Kim et al, 2015) induced oxidative stress.…”
Section: Faim Ko Cells Are Susceptible To Heat/oxidative Stress-inducmentioning
confidence: 99%
“…The two genes are not obvious candidate genes for phytosterol levels but they are involved in lipid metabolism. FAIM deficiency enhances SREBP signaling and promotes lipogenesis in liver 34 . FOXL2 represses expression of Star, a protein that controls cholesterol transport from the outer to the inner mitochondrial membranes 35 , 36 .…”
Section: Resultsmentioning
confidence: 99%